2021
DOI: 10.15547/ast.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and morphometric characterization of Bulgarian local chicken breed – Southwest Bulgarian dzinka

Abstract: Abstract. The poultry genetic resources of the Republic of Bulgaria cover mostly the domestic chicken and domestic pigeon species. A number of introduced breeds of chickens are bred in the country, but also some local primitive and decorative breeds. Southwest Bulgarian dzinka is one of the three bantam chicken breeds that originated in Bulgaria. The aim of the study is to make a complete exterior characteristic of the Southwest Bulgarian dzinka breed. A phenotypic evaluation of a total of 29 roosters and 61 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…In the current study, the weights of hens and cocks were statistically similar which contradicted the reports of Lukanov and Pavlova (2021), Assefa and Melesse (2018), Moula et al (2011) and Youssao et al (2010) in which males were rather heavier than females. The similarity in weights of male and female birds may be due to the slow growth rate of local chicken.…”
Section: Morphometric Trait Of Domestic Chickencontrasting
confidence: 97%
See 2 more Smart Citations
“…In the current study, the weights of hens and cocks were statistically similar which contradicted the reports of Lukanov and Pavlova (2021), Assefa and Melesse (2018), Moula et al (2011) and Youssao et al (2010) in which males were rather heavier than females. The similarity in weights of male and female birds may be due to the slow growth rate of local chicken.…”
Section: Morphometric Trait Of Domestic Chickencontrasting
confidence: 97%
“…In the current study, observation of longer beak lengths in males agreed with Lukanov and Pavlova (2021), Moula et al (2011) and Yakubu et al (2009) who reported that, the beaks of cocks were longer than hens.…”
Section: Morphometric Trait Of Domestic Chickensupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, indigenous chicken breeds are preserved by private breeders without commercial interests (Weigend et al., 2014). Scientific morphological comparisons have recently been made to accurately differentiate between breeds that appear roughly visually similar (Lukanov & Pavlova, 2021). Major problems in the small populations of indigenous chicken breeds include a rapid increase in inbreeding (Malomane et al., 2019), a lack of systematic performance testing and the absence of controlled breeding management (BLE, 2017).…”
Section: Introductionmentioning
confidence: 99%